Embryonic Folding - Donald Lowrie; Adam Schirmer; Karen Marsh (Association of American Medical Colleges, 2007)
Abstract Introduction Embryology is a challenging subject to learn because it involves three-dimensional structures within the embryo that are constantly changing as development proceeds. This animated module depicts embryonic folding, in which the flat embryonic disk transforms into a tube-shaped structure. Learners see the major features that occur during embryonic folding in both longitudinal and cross-sections through the developing embryo and extraembryonic membranes. Methods The module can be run as a self-progressing animation with an accompanying narration or be used in a more interactive fashion whereby the images can be paused, advanced, or reversed as the user wishes. Results We conducted a randomized, controlled study to test the effectiveness of the module. The control group did not have access to the animation, whereas the test group did. Both groups took a quiz and filled out an evaluation. There were 34 student volunteers for the study, and 29 of them completed all steps of the study-using the module (if in the test group), attending a lecture, and completing the quiz. Results from the written evaluations were positive. The test group showed better test scores, reaching statistical significance. Discussion Due to the small number of participants, we will continue the tests. We also plan to test for long-term retention.